Produção científica docente em tratamento temático da informação no Brasil: uma abordagem métrica como subsídio para a análise do domínio - Danuello, Jane Coelho [UNESP] (2007)
Aiming at characterizing the scientific production of professors in the area of Subject Treatment of Information – S.T.I., 77 Journal articles by 19 post-graduation professors acting in the field, were selected, so as to detect the characteristics of this production and information sources utilized by authors- professors which may provide a wider knowledge of the area as an academic acting space. From the information provided by these articles, a database encompassing fields such as author, title of the article, title of publication, keywords, citations, country, language, year of publication and institution of the author, was compiled. The VantagePoint software, which organizes the information allowing the generation of lists and data-crossing matrices, which in turn enable one to verify the existing relationships among the fields, was used. As for the productivity of authors-professors who are distributed in 5 universities (USP, UNESP, UFMG, UnB and UFF), a data analysis showed that group kept an average of 4 to 5 articles per year, from 1990 to 2006. These articles were published in four languages – Portuguese, English, Spanish and France – in 27 Journals of 9 countries, being 18 published in Brazil and a strong trend to publish in renowned and high quality Journals was seen. An analysis of the 817 references contained in the articles, revealed a total of 659 authors cited and a 50% preference for books, as an information source, as well as the predominance of classical authors of the area, used as a theoretical base. In addition, some 20% of the professors’ production in the literature used in the area, was identified, thus characterizing the impact and importance of this production for the field. The subjects approached were identified from the key-words utilized, demonstrating a predominance of interest for the processes of the area, being indexing the most frequent subject.